IMPLEMENTASI SISTEM VOUCHER DENGAN ROUTER MIKROTIK - Adhiwibowo, Whisnumurti; Mindatama, Wijatmoko (Jurnal Pengembangan Rekayasa dan Teknologi, 2019)
Voucher system is a feature owned by Mikrotik to facilitate network administrators to manage access on the router based on bandwidth allocation, website filtering and access time settings. This final project will be implemented voucher system at PT. Tunggul Sakti Sejahtera. The number of employees is approximately 25 employees at headquarters who own a smartphone and connect to the company's Access Point. Bandwidth allocation, website filtering and access time setting for each employee can not be limited. To solve the problem, the authors plan to implement a voucher system on the network of PT. Tunggul Sakti Sejahtera.Implementation method of voucher system used is CISCO Network Cycle PPDIOO method has Prepare, Plan, Design, Implement, Operate, and Optimize. Implementation of voucher system at PT. Tunggul Sakti Sejahtera uses router Mikrotik Routerboard 750 series and D-Link access point as a repeater device. Voucher system can optimize network management at PT. Tunggul Sakti Sejahtera so it can facilitate network administrator in managing computer network. Documentation of system is done periodically, if the system crashes it can be restored
Keywords: Voucher System; Mikrotik Router; PPDIOO Network Cycle